Route optimisation and solving Zermelo's navigation problem during long distance migration in cross flows. (5th December 2013) - Hays, Graeme C.; Christensen, Asbjørn; Fossette, Sabrina; Schofield, Gail; Talbot, Julian; Mariani, Patrizio
Abstract: The optimum path to follow when subjected to cross flows was first considered over 80 years ago by the German mathematician Ernst Zermelo, in the context of a boat being displaced by ocean currents, and has become known as the 'Zermelo navigation problem'. However, the ability of migrating animals to solve this problem has received limited consideration, even though wind and ocean currents cause the lateral displacement of flyers and swimmers, respectively, particularly during long‐distance journeys of 1000s of kilometres. Here, we examine this problem by combining long‐distance, open‐ocean marine turtle movements (obtained via long‐term GPS tracking of sea turtles moving 1000s of km), with a high resolution basin‐wide physical ocean model to estimate ocean currents. We provide a robust mathematical framework to demonstrate that, while turtles eventually arrive at their target site, they do not follow the optimum (Zermelo's) route. Even though adult marine turtles regularly complete incredible long‐distance migrations, these vertebrates primarily rely on course corrections when entering neritic waters during the final stages of migration. Our work introduces a new perspective in the analysis of wildlife tracking datasets, with different animal groups potentially exhibiting different levels of complexity in goal attainment during migration.